2018
DOI: 10.1186/s13046-018-0878-0
|View full text |Cite|
|
Sign up to set email alerts
|

Astragaloside IV inhibits lung cancer progression and metastasis by modulating macrophage polarization through AMPK signaling

Abstract: BackgroundAccumulating evidence suggests that M2-polarized tumor-associated macrophages (TAMs) play an important role in cancer progression and metastasis, making M2 polarization of TAMs an ever more appealing target for therapeutic intervention. Astragaloside IV (AS-IV), a saponin component isolated from Astragali radix, has been reported to inhibit the invasion and metastasis of lung cancer, but its effects on TAMs during lung cancer progression have not been investigated.MethodsHuman THP-1 monocytes were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(161 citation statements)
references
References 35 publications
5
146
0
Order By: Relevance
“…Many of the herbal medicine components in FLP ointment have antitumour effects. For example, ginsenoside Rg3 (Radix Panacis Quinquefolii) inhibits tumour migration and invasion through the PI3K-AKT signalling pathway [44] and may improve the sensitivity to cisplatin during lung cancer therapy [45]; liquiritin (Radix Glycyrrhizae) induces apoptotic cell death by upregulating p53 and p21 in A549 non-small cell lung cancer cells [46]; and calycosin, astragaloside VI, and formononetin (Radix Astragali) suppress A549 cell proliferation and migration through the induction of cell cycle arrest and apoptosis via the PKC-α/ERK1/2 pathway and the modulation of macrophage polarization through AMPK signalling [47][48][49]. us, these components are the basis for the inhibitory functions in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the herbal medicine components in FLP ointment have antitumour effects. For example, ginsenoside Rg3 (Radix Panacis Quinquefolii) inhibits tumour migration and invasion through the PI3K-AKT signalling pathway [44] and may improve the sensitivity to cisplatin during lung cancer therapy [45]; liquiritin (Radix Glycyrrhizae) induces apoptotic cell death by upregulating p53 and p21 in A549 non-small cell lung cancer cells [46]; and calycosin, astragaloside VI, and formononetin (Radix Astragali) suppress A549 cell proliferation and migration through the induction of cell cycle arrest and apoptosis via the PKC-α/ERK1/2 pathway and the modulation of macrophage polarization through AMPK signalling [47][48][49]. us, these components are the basis for the inhibitory functions in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…M2‐TAMs which are differentiated from THP‐1 cells have been extensively used to study M2‐polarized macrophage functions . THP‐1 cells were maintained in culture in Roswell Park Memorial Institute 1640 (RPMI 1640; Gibco, Invitrogen) culture medium containing 10% of fetal bovine serum (FBS; Gibco, Invitrogen) and supplemented with 2 mM l ‐glutamine (Sigma) at 37°C in a humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…2 | MATERIALS AND METHODS 2.1 | Cell culture and experimental treatments M2-TAMs which are differentiated from THP-1 cells have been extensively used to study M2-polarized macrophage functions. [12][13][14][15][16][17] THP-1 cells were maintained in culture in Roswell Park Memorial Institute 1640 (RPMI 1640; Gibco, Invitrogen) culture medium containing 10% of fetal bovine serum (FBS; Gibco, Invitrogen) and supplemented with 2 mM L-glutamine (Sigma) at 37°C in a humidified atmosphere of 5% CO 2 . To generate M2-TAMs, 1 × 10 6 THP-1 cells were treated with 100 ng/mL phorbol 12-myristate 13-acetate (PMA; MedChemExpress) for 24 hours, then incubated with 20 ng/mL interleukin-4 (IL-4; Novus Biologicals) for 48 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, antifungal drug itraconazole targets mitochondrial protein voltage-dependent anion channel 1 (VDAC1) to suppress angiogenesis by modulating the AMPK/mTOR signaling axis in endothelial cells [123]. Interestingly, there are some studies which have shown that AMPK activation by some agents may play a positive role in tumor growth, even including metformin [124,125].…”
Section: Ampk In Angiogenesismentioning
confidence: 99%